Design of Photo Catalog with Modern Minimalist Concept in Aiueos Studio Using Coreldraw X7 - Linda Norhan; Tedi Kustandi; Widya Jati Lestari (Jurnal Mantik, 2020)
Catalog is a graphic communication media in the form of a book which contains various types of products and prices. Catalog generally makes it easy for people to see a list of some of the information presented, it can be said also is a media of information that contains a list of a company's product collection that is systematically compiled so that it makes it easier for consumers to know the products they will choose or use. AIUEOS Photo Studio is as a research object because it does not have a catalog and consumers who come to AIUEOS Photo Studio don't really know much about what photo services AIUEOS Photo Studio has because the photo service information from the brochure is incomplete. Based on the above problems, an AIUEOS Studio Photo Catalog was made. The catalog aims to provide information about all services provided by AIUEOS Photo Studio, so consumers know that in addition to photo services there are other services, namely make up services, wedding packages, outdoor prewedding packages, camera rentals, camera lens rentals, camera flash rentals, rent kebaya, and dress rental. Catalog in printed form using a minimalist concept and postmodern style. The concept and style of this postmodern is very interesting so that it has a special attraction for those who see it. This catalog is used when visitors enter the Photo Studio. Before making a catalog, a storyboard has been made first after that it was applied using the Coreldraw x7 application, using a 150 gram and 100 gram paper or paper type of paper for the cover and contents of the catalog. Binding uses volumes of steples or saddle stitching. After experimenting with giving AIUEOS Studio catalogs to companies, consumers have a good view of choosing the photo services that they want to choose from and consumers can find out all the photo services available at AIUEOS Studio.